(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women represent a major share of those imprisoned each year in the United States for domestic violence (Miller, 2005). A Tennessee study, for example, has shown that 16 of the prisoners of violence are women (Feder Henning, 2005), while 35 in Concord, New Hampshire Women are women (Miller, 2005). Many of them are short-term offers such as a programme of batterer response or anger control (Miller, 2005). A substantial number of women recognised as physical abusses against their partners are also provided by the army. In one research by 2,991 airmen in the Air Force who had physically abused a wife, 23 of the convicts are women (Brewster, Milner, Mollerstrom, Saha, Harris, 2002). An further examination in the Central Registry of the Army data from 1989 to 1997 shows that women were 33 of those who committed domestic violence (McCarroll et al., 1999).This section analyses important findings from research on the use by women of violence against intimate males in support of those involved in the provision of aid to women and their families involved in domestic violence. This study discusses how the prevalence of women’s committees is contrasted with the presence of male committees how intimate relationship abuse prevails among military members the difference in gender in the physical and psychological consequences of domestic abuse among women sometimes varies from violence in males Violence at home. Violence at home